Optimalisasi Pengelolaan Limbah Organik melalui Budidaya Maggot Black Soldier Fly (BSF) di Padukuhan Balong - Fais, Rahman; Putri, Rusdita Nabila; Arbi, Muhammad Irfa’i Royyan; Kusumawardhana, Airlangga Pramudya; Tomaputra, Muhammad Bagas; Aulia, Ninda; Wandira, Sara; Setyaningrum, Luluk Dwi; Ramadhani, Rizka Khairunnisa; Kurniawan, Alfinsa Risky; Wijayanti, Septi Nur (Universitas Muhammadiyah Yogyakarta, 2025)
Group Discussions (FGD) and hands-on maggot cultivation practice. The educational component covers an understanding of the BSF life cycle and the benefits of maggot cultivation as a high-nutrient alternative livestock feed. In practice, the community is taught how to cultivate maggots from the egg stage to larvae and how to utilize them to reduce organic waste. The program results show that maggots can decompose approximately 80% of the organic waste provided, with faster growth rates observed in maggots fed carbohydrate-based waste compared to vegetable waste. Additionally, community participation was relatively positive, with several residents expressing interest in independently cultivating maggots. Despite the program’s success in increasing community awareness and skills, several challenges remain, such as low participation in maggot cultivation practices, limited access to maggot seeds, and odor management in the cultivation media. Therefore, more interactive educational strategies, improved seed availability, and better feed management are needed. Overall, maggot cultivation has the potential to be a sustainable solution for organic waste management, improving environmental cleanliness, and providing economic benefits for the residents of Padukuhan Balong